2019
DOI: 10.1016/j.omtn.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Dual Mechanisms of Action of Self-Delivering, Anti-HIV-1 FANA Oligonucleotides as a Potential New Approach to HIV Therapy

Abstract: Currently, the most effective and durable therapeutic option for HIV-1 infection is combination antiretroviral therapy (cART). Although cART is powerful and can delay viral evolution of drug resistance for decades, it is associated with limitations, including an inability to eradicate the virus and a potential for adverse effects. Therefore, it is imperative to discover new HIV therapeutic modalities. In this study, we designed, characterized, and evaluated the in vitro potency of 2′-deo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 48 publications
7
35
0
Order By: Relevance
“…According to the findings of Mayumi Takahashi et al . 46 , we confirmed that FANA oligos penetrate into the cells very easily. Then, for our experiments, a concentration of 8 µM of 2′F-ANA was chosen.…”
Section: Methodssupporting
confidence: 76%
“…According to the findings of Mayumi Takahashi et al . 46 , we confirmed that FANA oligos penetrate into the cells very easily. Then, for our experiments, a concentration of 8 µM of 2′F-ANA was chosen.…”
Section: Methodssupporting
confidence: 76%
“…One of the most important modification to the biological function of FANA ASO molecules is their ability to penetrate cells without the necessity of delivery vehicles required in transfection approaches. Our results revealed that FANA ASO molecules targeting CCL3 can indeed penetrate BMDMs in gymnotic fashion, as previously described for other cell types in vitro (Baby et al, 2020;Margiotta and Howard, 2020;Schmidt et al, 2019;Smaldone et al, 2019;Suwanmanee et al, 2019;Takahashi et al, 2019). We also demonstrated the successful suppression of CCL3 expression in BMDMs by CCL3 specific FANA ASOs.…”
Section: Discussionsupporting
confidence: 85%
“…FANA ASO mediated mRNA suppression was observed to the same extent in a model of Huntington's disease, where the suppression persisted for 12 weeks after continuous infusion for 2 weeks (Kordasiewicz et al, 2012). In vitro, sustained antisense activity has been described for other FANA ASO molecules for four to 13 days (Ferrari et al, 2006;Takahashi et al, 2019).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Lipid nanoparticles and viral vectors are being studied to ensure intracellular delivery. There has been some success in vitro using ASOs targeting HIV by targeting both viral and host factors and delivering them using a self-inactivating lentiviral vector system to HIV-infected human primary cells and producing strong suppression of HIV replication (103). HITS-CLIP found miR-122 binding directly to the 5'UTR of HCV protecting HCV RNA from degradation and promoting viral replication.…”
Section: Interactions Between Rna Viruses and The Hostmentioning
confidence: 99%